Quantitation of cytomegalovirus (CMV) DNA in leukocytes of human immunodeficiency virus-infected subjects with and without CMV disease by using PCR and the SHARP Signal Detection System. - Boivin, G (1997)
We report the development of a simple and rapid PCR assay for quantitation of the cytomegalovirus (CMV) DNA load in polymorphonuclear leukocytes. Using this system, a very good correlation was found between a high number of CMV copies in the blood and the presence of CMV disease in subjects with AIDS.